Plasma Levels of Tissue-Type Plasminogen Activator (tPA) in Normal Aging and Alzheimer's Disease: Links With Cognition, Brain Structure, Brain Function and Amyloid Burden - Tomadesso, Clémence; de Lizarrondo, Sara Martinez; Ali, Carine; Landeau, Brigitte; Mézenge, Florence; Perrotin, Audrey; de La Sayette, Vincent; Vivien, Denis; Chételat, Gaël (Frontiers in Aging Neuroscience, 2022)
Tissue-type plasminogen activator (tPA) is a protease known for its fibrinolytic action but is also involved in physiological and pathophysiological aging processes; including amyloid elimination and synaptic plasticity. The aim of the study was to investigate the role of tPA in cognitive and brain aging. Therefore, we assessed the links between tPA plasma concentration and cognition, structural MRI, FDG-PET and Flobetapir-PET neuroimaging in 155 cognitively unimpaired adults (CUA, aged 20-85 years old) and 32 patients with Alzheimer’s disease (ALZ). A positive correlation was found between tPA and age in CUA (p<0.001), with males showing higher tPA than females (p=0.05). No significant difference was found between ALZ patients and cognitively unimpaired elders (CUE). Plasma tPA in CUA negatively correlated with global brain volume. No correlation was found with brain FDG metabolism or amyloid deposition. Age-related tPA changes were associated to changes in blood pressure, glycemia and body mass index. Within the ALZ patients, tPA didn’t correlate with any cognitive or neuroimaging measures, but only with physiological measures. Altogether our study suggests that increased tPA plasma concentration with age is related to neuronal alterations and cardiovascular risk factors.